Fluidized bed application for component cleaning / Mohd Fauzi Hassim - Hassim, Mohd Fauzi (2005)
Cleaning process of metal parts becomes an imperative process in the industry and our daily life. For the example, the cleanliness of the machinery component is important to increase it efficiency instead to avoid it from breakdown. The lubricant used to the machine would transfer as the machine was operating. Additionally, the dust and soil from the environment made it worse. The conventional method of cleaning the metal parts are harmful to the operator and the environment else well. This is because the conventional cleaning process will used the chemical solvent. Therefore, the cleaning metal parts using the principle of fluidized bed is introduced that has been used for the combustion and heat treatment. This cleaning method is new technology and still in the development.